PENGARUH PENGGUNAAN MEDIA MONOPOLI TERHADAP HASIL BELAJAR PPKN PESERTA DIDIK KELAS IV SD MUHAMMADIYAH 18 - Harahap, Yusmaliani; Nasution, Hafizah Ayu Rizki; Thalia, Adinda Thalia; Amanda, Widya; Melyani Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of monopoly media on PPKn learning outcomes in class IV students at SD Muhammadiyah 18. This research is aquantitative research using an experimental method with a pretest-post test one group design. The data collection technique used is a test with a research instrument in the form of amultiple choice test. Prerequisite test data analysis techniques (normality test and hypothesis test). The normality test is carried out to determine whether the data obtained is normal or not, with the results that have been carried out, there are Pre Action results of 0.041 (normal) because sig < a (0.05 / 5%) and Post Action 0.051 (not normal) because sig > a (0.05 / 5%) and is included in the Shapiro Wilk. Meanwhile, hypothesis testing uses the